Vključevanje imigrantskih otrok v izobraževalni sistem - Bešter, Romana (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2009)
Integrating immigrant children into educational system. This article provides an overview and comparison of policies for integrating immigrant children into educational systems in selected EU Member States. It focuses in particularon the following questions: Do immigrant children have the same rights (and duties) to education as children who are citizens of host countries? Are there special programs for the admission of immigrant children into schools and for their integration into the regular educational process? Do immigrant children have the possibility to learn their mother tongue and the history and culture of their country of origin? Do the countries promote intercultural approach to education? Comparative analysis showed that the majority of countries studied allow all immigrant children (whatever their legal status) to have access to compulsory primary education. Also, all countries provide certain measures to assist in the integration of immigrant children into the regular educational process. Formally, the possibility for immigrant children to learn their mother tongue exists in most of the studied countries, in practice, however, several problems arise. Similar problems also occur in the transfer of the formally promoted intercultural approach and intercultural contents into the actual educational process.
Keywords: European Union; Evropska unija; imigranti; otroci; child; integracija; izobraževalni sistemi; school; šola